2008
DOI: 10.3163/1536-5050.96.3.005
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Informationist Specialty: A Systematic Review of the Literature

Abstract: While the informationist concept remains in the early adopter stage, it appears that domain knowledge, continuous learning, and embedding (working in context) are essential to success. The need for librarians to transition to greater specialization and libraries to emphasize customized service was underscored. A research agenda focused on information management, dissemination, behaviors, and economics is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 72 publications
1
76
0
Order By: Relevance
“…Davidoff & florence pointed out that this information resides in scattered formats with inconsistent indexing and accessibility and requires time, domain knowledge, retrieval, and critical appraisal skills to convey the best of it to the point of care 31 . Lindberg & Humphreys's futuristic vision of Medical libraries proposed a marked increase in electronic information but also more in-context work by librarians 'to improve quality, to reduce the risks associated with inefficient or incomplete retrieval of the available evidence, and to do community outreach' 32 .…”
Section: Challenges Before Health Librariansmentioning
confidence: 99%
“…Davidoff & florence pointed out that this information resides in scattered formats with inconsistent indexing and accessibility and requires time, domain knowledge, retrieval, and critical appraisal skills to convey the best of it to the point of care 31 . Lindberg & Humphreys's futuristic vision of Medical libraries proposed a marked increase in electronic information but also more in-context work by librarians 'to improve quality, to reduce the risks associated with inefficient or incomplete retrieval of the available evidence, and to do community outreach' 32 .…”
Section: Challenges Before Health Librariansmentioning
confidence: 99%
“…There is an abundance of studies on the impact of information professionals on various outcomes in the health sciences. For example, a systematic review by Rankin, Grefsheim, and Canto (2008) summarizes a number of studies on the impact of the informationist, defined as "a new professional… with responsibility for providing highly specialized information services in the clinical setting." Others have examined the impact of librarian services on clinical practices (McGowan, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other work has shown that clinical and service information resides in scattered formats; that there is unique literature held in individual databases requiring searching of multiple databases; that articles can be inadequately indexed; and that effective literature retrieval requires time and sophisticated skills [Sampson et al, 2008;Tieman et al, 2008, Tieman et al 2009Rankin et al, 2008. Further, different databases use different interfaces and default searching rules, making it unlikely that even experienced researchers will be both effective and efficient in finding all the literature they need.…”
Section: Why a Search Filter?mentioning
confidence: 99%